A collaborative model for school course module management using cloud computing platform - Nuhu, Musa Abdulbasit
Course Module Management (CMM) in schools is a formalized process of developing and coordinating teaching materials. Studies have proven that CMM is an essential feature used to handle course modules among school communities. A collaborative course module management is used to allow participants to collaborate and manage course modules via cloud technology that enables teacher interactions, sharing of course resources and learning from one another. Nowadays, schools do not have collaborative techniques to manage their course materials. Teachers usually use individual approaches to coordinate their course modules, and students are lacking of adequate learning resources to support their activities. This research aims to examine the current practices of course module management and propose a new collaborative model using Google's Platform as a Service (PaaS) environment. Raquel's interaction meta-model for Group, Task and Technology (GTT) contextual factors is adopted as the central framework of the new model. The Raquel' s interaction meta-model is a methodology that provides a systematic group structure functioning at higher level than the mere aggregation of member abilities and characteristics to perform required piece of works via a technological platform that can support spatial distribution and temporal patterning of group, task and technology interactivity. The process consists of the interaction that occurs among the group of users, the tasks being conducted and the cloud technology which are integrated using Adaptive Structuration Theory (AST), Coordination Theory (CT) and Task-Technology Interaction Theory (TTIT). The AST defined how the group interacted with the technology and the effects on the collaborative processes. The CT elaborated the act of working together harmoniously to perform and manage tasks to achieve a goal. The TTIT signified how the mediated groups yield effective task performance through idea generation and cognitive collaborative tasks that are supported by the technological platform's capability to deliver the desired goals. By using an empirical approach, the new proposed model is evaluated using questionnaire survey and four cloud quality of service (QoS) metrics. The results show that the model has accomplished the metrics of efficiency of 87.0%, effectiveness of 80.5%, learnability of 87.5% and attractiveness of 86.3%. The proposed model helps to facilitate a collaborative approach for CMM in schools. It provides a reliable collaborative platform among the collaborating group, the module tasks and the technology platform to help the educational community to handle the CMM difficulties.